2006
DOI: 10.1562/2005-07-15-ra-612
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Photostabilizer Having Built‐in Antioxidant Functionality and Its Utility in Obtaining Broad‐spectrum Sunscreen Formulations†

Abstract: Di-2,2'-diethylhexyl-3,5-dimethoxy-4-hydroxy-benzylidenemalonate (INCI name diethylhexyl syringylidene malonate, DESM), the target photostabilizer, was synthesized in one step by condensation of 3,5-dimethoxy-4-hydroxy benzaldehyde (Syringaldehyde) with di-2,2'-diethylhexyl malonate. Photostability data in sunscreen formulations showed that DESM is photostable and improves the photostability of avobenzone significantly when compared to control (without a photostabilizer). Photostable broad-spectrum sunscreen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Available substances are not completely efficient to neutralize free radicals generated by avobenzone photofragmentation (Chatelain and Gabard, 2001 Abbreviations: 3T3 NRU-PT, 3T3 Neutral Red Uptake Phototoxicity Test; BMTZ, bemotrizinol; BZP-3, benzophenone-3; AVO avobenzone, butyl methoxydibenzoylmethane; DNA, deoxyribonucleic acid; DMSO, dimethyl sulfoxide; DMEM, Dulbecco's Modification of Eagle's Medium; F1-F4, formulations 1-4; F1RP-F4RP, formulations 1-4 containing Retinil Palmitate; IC50, half maximum inhibitory concentration; HPLC, High Performance Liquid Chromatography; ICDRG, International Contact Dermatitis Research Group; LOQ, limit of quantitation; MPE, mean photo effect; MED, minimal erythema dose; OCT, octocrylene; OMC, octyl methoxycinnamate; OECD, Organisation for Economic Co-operation and Development; PBS, phosphate buffered saline; PIF, photo irritant factor; ROS, reactive oxygen species; RP, retinyl palmitate; UV, ultraviolet; UVA, ultraviolet A; UVB, ultraviolet B; k, wavelength. Bemotrizinol (bis-ethylhexyloxyphenol methoxyphenyltriazine, k = 280-380 nm) is a UV-filter, but it also shows promising results as an avobenzone photostabilizer (Chatelain and Gabard, 2001). It is able to absorb UV photons and it has been shown to improve the photostability of sunscreen formulations containing the combination octyl methoxycinnamate/avobenzone (Chaudhuri et al, 2006). Photostability evaluation studies are usually performed using quantitative separation techniques as High Performance Liquid Chromatography (HPLC) Deflandre and Lang, 1988;Berset et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Available substances are not completely efficient to neutralize free radicals generated by avobenzone photofragmentation (Chatelain and Gabard, 2001 Abbreviations: 3T3 NRU-PT, 3T3 Neutral Red Uptake Phototoxicity Test; BMTZ, bemotrizinol; BZP-3, benzophenone-3; AVO avobenzone, butyl methoxydibenzoylmethane; DNA, deoxyribonucleic acid; DMSO, dimethyl sulfoxide; DMEM, Dulbecco's Modification of Eagle's Medium; F1-F4, formulations 1-4; F1RP-F4RP, formulations 1-4 containing Retinil Palmitate; IC50, half maximum inhibitory concentration; HPLC, High Performance Liquid Chromatography; ICDRG, International Contact Dermatitis Research Group; LOQ, limit of quantitation; MPE, mean photo effect; MED, minimal erythema dose; OCT, octocrylene; OMC, octyl methoxycinnamate; OECD, Organisation for Economic Co-operation and Development; PBS, phosphate buffered saline; PIF, photo irritant factor; ROS, reactive oxygen species; RP, retinyl palmitate; UV, ultraviolet; UVA, ultraviolet A; UVB, ultraviolet B; k, wavelength. Bemotrizinol (bis-ethylhexyloxyphenol methoxyphenyltriazine, k = 280-380 nm) is a UV-filter, but it also shows promising results as an avobenzone photostabilizer (Chatelain and Gabard, 2001). It is able to absorb UV photons and it has been shown to improve the photostability of sunscreen formulations containing the combination octyl methoxycinnamate/avobenzone (Chaudhuri et al, 2006). Photostability evaluation studies are usually performed using quantitative separation techniques as High Performance Liquid Chromatography (HPLC) Deflandre and Lang, 1988;Berset et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies about how improvement of photostability may be obtained, e.g. with nanoparticle encapsulation of EHMC [23], liposphere preparation of BMDBM [24] or a combination with diethylhexyl syringylidene malonate and BMDBM [25]. These findings are very interesting and will hopefully lead to an improvement in photostability in commercial available products.…”
Section: Discussionmentioning
confidence: 99%
“…Photostabilizers have also been shown to exhibit antioxidant properties. Chaudhuri et al showed that diethylhexyl syringylidene malonate can be used as a photostabilizer for avobenzone as well as an effective antioxidant [5]. Synthetic antioxidants are also a possibility.…”
Section: Antioxidantsmentioning
confidence: 99%